Theoretical Validity of Problem Focused-Coping Skill Guideline to Develop Students’ Critical Thinking Skills - Hidayah, Nur; Yuliana, Anis Tri; Hanafi, Husni (Jurnal Kajian Bimbingan dan Konseling, 2020)
Critical thinking skills are central for students to become human resources with character. The process of developing thinking skills is currently done contextually within the implementation of learning materials, while critical thinking skills are also needed in everyday life situations. Developmental counselling services through the Problem Focused-Coping Skill (PFCS) strategy are an alternative to foster critical thinking skills through contextual situations in students’ daily lives. Anchored by a research and development model through preliminary studies, product development, and expert validation, the present study unraveled the theoretical validity of PFCS strategy to enhance students’ critical thinking skills. Participants involved were evaluators of product feasibility, namely counselling experts, learning media experts, and prospective users. Analysis of the assessment employed descriptive statistics and Aiken acceptance analysis. The results showed that: (1) there was a need for product development based on literature review and empirical data, (2) the PFCS strategy has been successfully developed in the form of format and content in the developmental service function to build high school students’ critical thinking skills, (3) the assessment of the counselling experts, learning media experts, and users show the validity index in the appropriate and acceptable categories. The theoretical feasibility of the product refers to the conditions, objectives, and processes in the PFCS strategy which accommodates thinking processes in problem solving and information management through students’ critical thinking skills.